The Origins of the Communist Rule in Eastern Europe: A Brief History (Journal of International Studies, 2020)
The history of communist rule is long and varied. Communism as a ruling system emphasizes on economy and balanced distribution of wealth and ownership of property among all the people. This system originated from the ideology of Karl Marx in 1845. Communist system in Eastern Europe was fostered by Soviet Union after the fall of Nazism at the end of World War II. This paper focuses on how the Eastern European states fell under the influence of Communist after World War II. It discusses how salami tactics were used by Soviet Union as one the methods to establish communist government in Eastern Europe. It also shows that Soviet Union’s position as a super power in Eastern Europe enabled her to spread communist ideology in the region.